Predicted probability of meniscus tears: comparing history and physical examination with MRI (Swiss Medical Weekly, 2011)
BACKGROUND: The indication for surgical treatment of a meniscal lesion should not only rely on magnetic resonance imaging (MRI) findings, but also on a detailed history and a thorough clinical examination. However, various intra-articular lesions may often produce similar symptoms. So, what kinds of symptoms are more associated with a meniscal tear? Is MRI worth doing? OBJECTIVE: The aims of this study were to identify sensitive and specific clinical tests and elements of patients’ history with a high predictive value, and to assess the combined diagnostic accuracy of sensitive and specific clinical tests and elements of patients’ history with MRI. METHODS: Data from 281 consecutive knee arthroscopies to investigate and treat suspected internal knee pathologies were retrospectively collected between March 2009 and April 2010. The study group consisted of 262 knees. Statistically significant factors in the clinical diagnosis of meniscal tears were screened by a chi-square test. Logistic regression analysis was used to determine which factors associated with meniscal tears found during arthroscopy. The diagnostic values of MRI and the sensitive and specific clinical tests and elements of patients’ history with high predictive value for meniscal tears were calculated. RESULTS: The overall diagnostic value of MRI for meniscal tears was: accuracy, 88.8%; sensitivity, 95.7%; specificity, 75.8%; positive predictive value (PPV), 88.2%; and negative predictive value (NPV), 90.4%. Giving way, locking and McMurray’s test were independent diagnostic factors with a predicted correct percentage of 80.0% (p